2022
DOI: 10.1021/acs.chemmater.2c01168
|View full text |Cite
|
Sign up to set email alerts
|

Conjugating Ligands to an Equilibrated Nanoparticle Protein Corona Enables Cell Targeting in Serum

Abstract: Targeting ligands are conjugated onto nanoparticles to increase their selectivity for diseased cells. However, they become covered by serum proteins which prevent them from binding to target receptors. Here, we show that the nanoparticle protein corona achieved a maximum thickness in serum because the protein adsorption and desorption rates reached an equilibrium. Simulation experiments suggest that the number of molecular interactions between proteins decrease with distance from the nanoparticle surface until… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 47 publications
0
21
0
Order By: Relevance
“…We next tested whether the adsorbed antibody would exchange with other proteins after incubation in full mouse serum. 36,37 FITC-conjugated aCD47 was first adsorbed onto the surface of MSN and incubated in full mouse serum for different time periods. The supernatant was collected after centrifugation, and the fluorescence was measured.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We next tested whether the adsorbed antibody would exchange with other proteins after incubation in full mouse serum. 36,37 FITC-conjugated aCD47 was first adsorbed onto the surface of MSN and incubated in full mouse serum for different time periods. The supernatant was collected after centrifugation, and the fluorescence was measured.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, we found that the size and zeta potential of aCD47-DMSN could be maintained almost constant in both phosphate buffer saline (PBS) and 10% fetal bovine serum (FBS)-supplemented PBS for over 72 h (Figure e,f). We next tested whether the adsorbed antibody would exchange with other proteins after incubation in full mouse serum. , FITC-conjugated aCD47 was first adsorbed onto the surface of MSN and incubated in full mouse serum for different time periods. The supernatant was collected after centrifugation, and the fluorescence was measured.…”
Section: Resultsmentioning
confidence: 99%
“…Conjugation to protein corona. The last strategy involves attaching targeting moieties to the surface of corona-coated NPs 108 (Fig. 2d).…”
Section: Targeting Strategies For Therapeutic Nanomedicinementioning
confidence: 99%
“…The targeting species can be attached to the formed protein corona in an equilibrium state -when the protein corona is formed within a controlled single-component or multicomponent biofluid that does not change over time. For example, both bare and corona-coated gold and silica NPs were functionalized with transferrin, and their targeting capacities towards cells with transferrin receptors were monitored in the absence and presence of serum proteins 108 . Although the targeting capacity of transferrin-conjugated bare gold and silica NPs in the presence of serum was reduced compared with the serum-free media, there was no evidence of targeting efficacy reduction when transferrin was conjugated to the equilibrated protein corona of gold and silica NPs.…”
Section: Targeting Strategies For Therapeutic Nanomedicinementioning
confidence: 99%
“…Surface chemistry plays a critical role in endowing colloidal stability and interfacial functionalitythese factors determine how nanoparticles adapt to the chemical or environmental stimuli and thus manifest in interparticle crosslinking and colorimetric sensing. , The depth and diversity of the ligand field provide choices spanning from metal complexes, small organic compounds, , polymers, , and other biomacromolecules ( e.g. , peptides, ,, proteins, oligonucleotides). These can tailor the versatile interfaces between nanoparticles and biological systems.…”
Section: Introductionmentioning
confidence: 99%